Hubungan Motivasi Belajar Dengan Hasil Belajar Mata Pelajaran Tata Hidang Kelas XI Di SMK Negeri 3 Solok - Eka Wahyuni; Elida Elida (Jurnal Pendidikan Tata Boga dan Teknologi, 2020)
This research is motivated by the low student learning outcomes in the Subjects in Class XII Catering Services. This study aims to 1) Describe the learning motivation of class XI students in state Vocational High School 3 Solok, 2) Describe the learning outcomes of class XI students in State Vocational High School 3 Solok, 3) Describe the relationship of motivation with student learning outcomes in Subjects in State Vocational School 3 Solok. This type of research is quantitativedescriptivewithacorrelationalapproach.Thepopulationinthisstudywereallstudents of catering services, namely class XII catering services at SMK Negeri 3 Solok, amounting to 60 people with a sample of 60 people using total sampling techniques. The instrument used in this studywasaquestionnaireusingalikerscalethathadtesteditsvalidityandreliability.Thenthedata is analyzed through analysis of descriptions and correlations using formulas and calculated manually and SPSS. The results showed that overall student motivation was in the moderate category.Thereisastrongandsignificantpositiverelationshipbetweenmotivationandlearning outcomesintheSubjectsofClassXIICateringServicesatSMK Negeri3Solok